Do Socio-Economic Conditions Influence Dynastic Politics? Initial Evidence from the 16th Lok Sabha of India - Cruz, Jan Frederick (Archīum Ateneo, 2015)
This study contributes to the literature on political dynasties and their links to economic development by focusing on the case of India, in particular the members of the parliament (MPs) of sixteenth Lok Sabha (i.e., the lower house of the Indian parliament). It is notable for it marked a decline in the dominance of the Indian National Congress in the country's political scene. The Congress party, once led by India's founding fathers Mohandas Gandhi and Jawaharlal Nehru, has long been dominated by the political family started by Nehru’s daughter Indira Gandhi. The situation of India mirrors the politics of other countries in South Asia, where the national governments are -- or were -- led by entrenched ruling families: the Bhuttos of Pakistan; the Bandernaikes of Sri Lanka; the Koirala family of Nepal; and the Sheikh Mujib dynasty of Bangladesh. The research hypothesizes that state-level socio-economic indicators influence dynastic representation to the Lok Sabha. The results of the study do not claim causation but suggest the existence of patterns and relationships worth exploring in future studies. These patterns are then compared to the Philippine case.